Critical Impact Energy of Flat Nose Hard Projectile Causing Early Scabbing in Concrete Slab - Dr. Qadir Bux alias Imran Latif; Assoc. Prof. Dr. Ali Al Nuaimi; Prof. Dr. Ismail Abdul Rahman; Prof. Dr. Ahmad Mujahid Ahmad Zaidi (Institute of Advanced Engineering and Science, 2014)
In this paper, 2D numerical simulation finite element analysis has been carried out for critical impact energy of flat nose hard projectile causing early scabbing in concrete slab, based on reflected stress wave propagation with elastic assumption of the classic wave equation, using ABAQUS software. Numerical simulation predictions were compared with experimental data and with the well established UMIST, NDRC, Li and Reid formulae and found comparable and reliable. The influence of hard projectile diameter with flat nose, and concrete wall thickness on critical impact energy was also investigated. It was found that the effect of critical impact energy is directly proportional to the thickness of concrete target and inversely proportional to the diameter of flat nose hard projectile.